Clinical assessment of computed tomography guided radiofrequency ablation in the treatment of inoperable patients with pulmonary tumors - Chen, Tianming; Jin, Jiewen; Chen, Shilin (Journal of Thoracic Disease, 2017)
Background: To enhance our understanding of the feasibility, effectiveness, safety and quality of life (QoL) of radiofrequency ablation (RFA) for inoperable patients with pulmonary tumors. Methods: The data of 88 patients with pulmonary tumors undergoing RFA were collected. Proof of malignancy was obtained by biopsy in all patients. Diagnoses included non-small cell lung cancer (NSCLC) in 74 patients and pulmonary metastases in 14 patients. Patients underwent computed tomography (CT)-guided RFA according to standard protocol and had a 2-year follow-up. Results assessment included feasibility (correct placement of the ablation probe into all targeted tumors), effectiveness (overall survival rate and local control rate), safety (treatment-related complication and changes in pulmonary function) and QoL. Results: One hundred and thirty-four RFAs were successfully conducted in 88 patients with 96 nodules. Correct placement of ablation probe into targeted tumors with completion of the planned treatment protocol was feasible in all 88 (100%) patients and no procedure-related deaths occurred. Major complication rate was 4.5% (4/88), which consisted of symptomatic pneumothorax (2/88) and high fever (2/88). No significant worsening of pulmonary function was observed. Tumors shrank obviously at 6 months after RFA with a statistically significance (P